Volatile organic compounds in feminine hygiene products sold in the US market: A survey of products and health risks. (November 2020) - Lin, Nan; Ding, Ning; Meza-Wilson, Emily; Manuradha Devasurendra, Amila; Godwin, Christopher; Kyun Park, Sung; Batterman, Stuart
Graphical abstract: Highlights: All FHPs in this study contained some toxic VOCs but generally at low concentrations. should be addressed Product labels did not indicate VOC concentration and composition. Risks associated with some of the FHPs should be addressed. We recommend elimination of toxic VOCs and disclosure of ingredients. Abstract: Feminine hygiene products (FHPs) are used on highly permeable and sensitive vaginal and vulvar tissues by many women. These products contain a variety of chemicals, and few regulations require disclosure of their ingredients. The objectives of this study are to identify volatile organic compounds (VOCs) that may be present in these products and to evaluate the potential for exposure and health risk associated with product use. We collected 79 commercially available FHPs, including washes, tampons, menstrual pads, wipes, sprays, powders and moisturizers, and analyzed their composition using purge and trap sampling, thermal desorption, gas chromatography and mass spectroscopy. Exposures and risks were modeled using reasonable upper bound exposure scenarios. The highest VOC concentrations (as total target VOCs) were found in washes, sprays and powders, with median concentrations from 25, 000 to 34, 000 ng/g. Benzene (maximum: 3, 604 ng/g) was detected in 83% of the collected products, and 1, 4-dioxane (maximum: 24, 354 ng/g) in 50% of the products. VOC composition depended on the FHP type, manufacturer and brand. Products labeled as "organic, " "natural, " or "for sensitive skin" did not necessarily have lower VOC concentrations. For most FHPs, calculated risks were low; however, menstrual pads had hazard ratios of up to 11, sprays and powders had hazard ratios of up to 2.2 and excess cancer risks of up to 2.1 × 10 -6, and washes had excess cancer risks of up to 3.3 × 10 -6 . Our data suggest that all tested FHPs contained some toxic VOCs, and that risks of using some products should be addressed. We recommend the elimination of toxic ingredients and the disclosure of all chemicals that are used in these products.